The Impact of Utilizing the Social Interactive Writing for English Learners (SWELL) Approach on EFL Learners Writing Skills - Pramudita, Bintang; Manurung, Yayuk Hayulina (Universitas Pahlawan Tuanku Tambusai, 2023)
This research aimed to determine the impact of utilizing the social interactive writing for English language learners (SWELL) approach on EFL learners' writing skills, especially in writing analytical exposition text. This research was conducted during the academic year 2022/23 at SMK PAB 2 Helvetia Medan. This quantitative research was conducted using an experimental research design. The subjects of the research were 44 eleventh-grades students from SMK PAB 2 Helvetia Medan who were selected using a total sampling technique and then divided into two groups. The data were acquired using a pre-test and a post-test, and then analyzed using the t-test formula in the SPSS version 22 program. The difference between the post-test mean scores of the control and experimental groups was 77.57 and 84.40. The findings of this study indicate that the SWELL method is more effective than the Teacher-Centered method in improving students' writing abilities in exposition texts at SMK PAB 2 Helvetia, where the SWELL method was implemented.